Research Advancements in Food Satiety and Its Testing Methods - YAO Mengli, HAN Xiaofeng, WANG Ruoyong, HAN Xiaowei, HAN Zhong, ZENG Xin’an, HUANG Jingmei, LIU Yifeng, YUAN Peng, LIU Jia, DUAN Shenglin (Shipin Kexue)
Satiety, defined as the state of satisfaction and the end of desire to eat after a meal, is of great significance in maintaining normal appetite, regulating body mass, preventing obesity, and improving metabolic diseases. This article systematically analyzes various factors influencing satiety, encompassing food composition, sensory attributes, energy density, psychological factors, and dietary behaviors. It further elucidates the mechanisms by which these factors contribute to satiety. Additionally, the focus of this article is on introducing the application of emerging technologies in satiety assessment such as the visual analog scale, gastrointestinal hormone measurements, and scintillation scanning, which demonstrate scientific rigor and effectiveness in evaluating satiety. The present article discusses the significance of research on satiety and testing techniques and points out future prospects. Ultimately, it aims to provide theoretical underpinnings and practical guidance for in-depth exploration of the satiety mechanism, innovation in satiety testing techniques, and the development of high-satiety food products.